Strategi Pengembangan Potensi Pariwisata melalui Pendekatan Community Based Tourism (CBT) Desa Carang Wulung Kecamatan Wonosalam Kabupaten Jombang - Rohimah, Afifatur; Hariyoko, Yusuf; Ayodya, Beta Puspitaning (Jurnal Ilmiah Administrasi Publik, 2018)
Tourism is the main sector to replace oil and gas from the Republic of Indonesia, therefore the government is focusing on managing tourism with a communitybased system and management. The Community Based Tourism (CBT) system is one of the tourism management solution systems that are expected to be able to develop the tourism potential of each region. In the CBT system, communities around tourist attractions are the determinants of the success of tourism development itself, because the community will be fully involved in planning, management and development. In Carang Wulung Village, Wonosalam Subdistrict, Jombang District, the application of CBT system has not been optimally implemented because the skills of the people in tourism management are still minimal, and government support is not optimal.